PENINGKATAN BERPIKIR KRITIS MELALUI E-MODUL SISTEM SARAF BERBASIS EXE LEARNING UNTUK PENDIDIKAN BERKELANJUTAN - Putri Karmila, Pina Putri Karmila; Saiman Rosamsi (Biosfer : Jurnal Biologi dan Pendidikan Biologi, 2025)
Critical thinking is an essential 21st-century skill that must be developed in biology,learning, especially in complex topics such as the nervous system. This study aims to analyze the effectiveness of a nervous system e-module based on exe learning in improving students’ critical thinking skills as part of the implementation of sustainable education. The research employed a quasi-experimental method with a Nonequivalent Control Group Design. The subjects were two eleventh-grade classes selected through purposive sampling, consisting of an experimental class and a control class. The research instruments included essay tests based on Ennis’ five indicators of critical thinking, and a questionnaire to assess students’ responses. Data were collected through pretests, posttests, and questionnaires, then analyzed using normality tests, homogeneity tests, t tests, and gain scores. The results showed that the exe learning-based e-module significantly improved students’ critical thinking skills. The experimental class achieved an N-Gain score of 0.70 (high category), while the control class scored 0.23 (medium category). Improvement occurred across all indicators of critical thinking. Statistical tests confirmed that the data were normally distributed, homogeneous, and showed significant differences between the two groups. Students’ responses to the e-module were highly positive in terms of appearance, ease of use, and content attractiveness. Therefore, the exe learning-based e-module is proven to be effective in enhancing critical thinking skills and supporting innovative and sustainable learning.